Finding Biomarkers from Long-Non-Coding RNAs in Serum of Patients with Non-Alcoholic Fatty Liver Disease - Yonis, Nouran (AUC Knowledge Fountain, 2022)
Nonalcoholic fatty liver disease (NAFLD) is becoming a serious global public health problem as it is a highly prevalent condition, that begins as simple liver steatosis and develops into an inflammatory steatosis form known as non-alcoholic steatohepatitis (NASH). NAFLD has been linked with multiple comorbidities, which in certain cases predisposes to mortality secondary to extrahepatic neoplasms and coronary diseases. On the other hand, NASH leaves patients at risk of developing hepatocellular carcinoma (HCC). The incidence of NAFLD- based HCC is steadily increasing and is projected to surpass the incidence of HCC from viral origins. Long non-coding RNAs (lncRNAs) have been recently used as biomarkers for predicting various diseases. This research study intended to use bioinformatics computational analysis of microarray and sequencing databases to identify a differentially expressed panel of lncRNAs in the serum of NAFLD patients relative to samples from healthy individuals. Five differentially expressed lncRNAs (SNHG17, H19, MEG3, DUBR, and PVT1) were obtained from the bioinformatic analysis. Real-time polymerase chain reaction (PCR) was used to measure the levels of expression of these lncRNAs in the serum of 20 healthy individuals, 62 NAFL patients, and 30 NASH patients. The results of this study showed a highly significant increase in serum concentration of H19, MEG3, DUBR, and PVT1 in NAFL patients compared to healthy individuals (P Using a combined panel of four lncRNAs improved the overall sensitivity and specificity of NAFL detection to 73.81% and 100% respectively, and NASH diagnosis to 73.33% and 95% respectively. Moreover, a combined panel of H19 and PVT1 possess potential diagnostic power for early detection of NAFL and NASH with an accuracy of 98.39%, and 88% respectively. Further investigation is required to assess the therapeutic effects of these lncRNAs in NAFLD. In conclusion: Using a combined lncRNAs panel (H19, MEG3, DUBR, and PVT1) could serve as a non-invasive biomarker for early detection of NAFLD. A novel lncRNA panel (H19, MEG3, DUBR, and PVT1) was introduced to establish a potentially definitive and minimally invasive diagnostic test that can detect the disease at an early stage of its progression.